Penerapan Manajemen Risiko Pada UMKM XYZ - Fatma Dwi Jati (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2023)
This research aims to map the risks faced by XYZ MSMEs located in Medan. The analytical method used in this research is a case study and descriptive qualitative research method which was carried out using interviews and FGDs with managers and employees of UMKM XYZ. Based on the results of the analysis carried out, six risks were identified. The six risks have been identified and analyzed using stages according to ISO 31000: 2009 and recommendations for their control are considered. Based on the stages that have been carried out, written and formal risk management is prepared which can then be implemented in the operations of MSME XYZ.